Respostas

2014-02-07T00:23:30-02:00
A)-5^0+3^0 - (-4)^0 =  
      1  +  1  -  1
       2  -  1
          1                                                                                                   

B)√1/25 +(0,17)^0 =
      1/5  + 1
      1/5  +  1/1
         1  + 5   = 6                                                                                               
            5          5       
       
C)2^0 +1/2  = 
     1  +  1/2
     1/1 + 1/2
      2  +  1   = 3                                                                                                  
          2          2

 1/4 - 2^0=
1/4 - 1
1/4 - 1/1
1  -  4 = 3
    4       4

2014-02-07T00:50:29-02:00
Olá
A)-5^0+3^0 - (-4)^0 =   
       -1+1-1 =1  
                                                                                                
 B)√1/25 +(0,17)^0 =
       1/5+1= 6/ 5
         
          C)2^0 +1/2                                                                                    
         1  +  1/2= 
           2+1/2=3/2                                                                                                    
1/4 - 2^0=
1/4-1=4-1
 =+3/4